Semi-transparent biomass-derived macroscopic carbon grids for efficient and tunable electromagnetic shielding. (November 2018) - Chen, Zeping; Yi, Da; Shen, Bin; Zhang, Lihua; Ma, Xiaohui; Pang, Yongyan; Liu, Li; Wei, Xingchang; Zheng, Wenge
Abstract: High-performance electromagnetic interference (EMI) shields are urgently needed due to the rapid development of modern electronics industry. Herein, biomass-derived highly conductive macroscopic carbon grids (MCGs) were fabricated through the carbonization of wood-pulp fabric matting. The resultant MCGs with thickness of ∼0.3 mm exhibited not only exceptional EMI shielding effectiveness (SE) of ∼20.3–45.5 dB positively related with their carbonization temperature or negatively associated with their empty grid size, but also semi-transparent characteristic with the transparency of ∼15%–56% originated from their grid-like configurations. Moreover, an accurate EM model was constructed for the SE simulation of the MCGs in the 3-D full-wave simulation. Furthermore, it is demonstrated that the EMI SE of double-layered MCG sample could be conveniently tuned by changing the interleaving degree of the stacked grids through tiny translational motion under constant thickness, showing potential for the design of EM attenuating devices with tunable performance. Graphical abstract: Image 1